USE OF MOTHER LANGUAGE AS A COMMUNICATION TOOL INTRODUCING INDONESIAN LANGUAGE AT AL-IMAN TERONG KINDERGARTEN EAST ADONARA DISTRICT: PENGGUNAAN BAHASA IBU SEBAGAI ALAT KOMUNIKASI PENGANTAR BAHASA INDONESIA DI TK AL-IMAN TERONG KECAMATAN ADONARA TIMUR - Margaret P.E. Djokaho; Anisa Tul Azizah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The use of mother tongue (Lamaholot language) in daily communication both in the family, community and school environment. The use of mother tongue as a means of communication between students at Al-Iman Terong Kindergarten and teachers. The mother tongue becomes an introduction to Indonesian language by the teacher so that students are able to understand the purpose and objectives of each learning process carried out. In this situation, cognitive and language development in obtaining fluency in Indonesian will be hampered or have difficulty. Therefore, mother tongue is used to solve the above problems, especially the use of local language (Lamaholot). The use of local language as a mother tongue in the classroom can be a tremendous support for students learning Indonesian as a second language. It is concluded that the use of mother tongue plays an important role in children's language and cognitive development. The use of mother tongue in the learning process allows students to gain total language experience and further the child's cognitive development and language development. Mother tongue as the language of instruction of Indonesian that children can understand and the use of mother tongue to improve cognitive development and language development of children..